Cold elastic and reactive atom-molecule collisions in helium--helium--alkali-metal triatomic systems - Suno, Hiroya; Esry, B. D. (My University, 2014)
Atom-molecule collisions in helium–helium–alkali-metal triatomic systems at cold energies are studied using the adiabatic hyperspherical representation. We consider the elastic collision processes 4HeX+4He→4HeX+4He and 4He2+X→4He2+X, as well as the reactive collision processes 4HeX+4He⇌4He2+X, where X is one of the bosonic alkali-metal atoms: 7Li, 23Na, 39K, 85Rb, or 133Cs. The elastic and reactive collision cross sections are calculated at nonzero collision energies by including not only zero atom-molecule relative angular momentum, L=0, processes but also L>0 processes. The total cross section for 4HeX+4He→4HeX+4He is found to increase with the scattering length between 4He and X, while the other collision processes are not found to have any systematic dependence on the alkali-metal species X.